Sistem Manajemen Penjadwalan Pengajaran Dosen berbasis SMS Gateway - jeffry, jeffry; Velayaty, Ali Akbar; Aziz, Firman (Universitas Pancasakti, 2023)
To improve performance in teaching time, one of which is by being punctual in teaching, therefore a system is needed to remind lecturers when teaching time arrives. Along with the development of technology, almost everyone has a communication device called a cell phone, one of the functions that are often used is sending messages or SMS. SMS Gateway is a platform that can be used to send and receive SMS whose settings can be made using PHP with data storage tools in the form of MySQL. Reminder SMS and teaching schedule monitoring using the SMS Gateway is a system used to remind lecturers about class schedules via SMS that was developed using the PHP programming language.